Task-Based Language Teaching (TBLT) and Its Relationship to Language Acquisition - Bakori, Hoda.A. (Scientific Journal of University of Benghazi, 2021)
Language teaching approaches and methods have garnered much attention in language teaching theory and practice. There are still many controversies about their usefulness and appropriateness. One of these approaches is known as the task-based language teaching approach (TBLT), which emerged in the 1990s. In this approach, teachers give 'tasks' rather than teaching an item of language (i.e. structure or form) according to the traditional methods of language teaching (e.g. the Presentation-Practice-Production model). Teaching a lesson using tasks needs careful consideration of the age and interests of the learners. The current paper provides an overview of some useful theoretical and pedagogical information on task-based language teaching (TBLT), such as the theoretical rationale for task-based language teaching. The paper also highlights the limitations and potential pitfalls of task-based language teaching as well as the main factors that need to be taken into consideration in planning task-based lessons. All of these points will be considered in this paper.